Adaptive Hospitality: Designing Modular Hotel Rooms for Multi-Functional Use in Urban Micro Hotels - Gani Ourooj Fatima; Deepti Pande Rana (International Journal of Architectural Design and Planning, 2026)
This research investigates the concept of adaptive hospitality through the lens of modular design, focusing on the creation of multi-functional hotel rooms in urban micro-hotel settings. With the rise in urban populations and increasing scarcity of land, hospitality design must adopt innovative spatial strategies that prioritize flexibility, efficiency, and user experience The research explores how modular and transformable design solutions can respond to the spatial constraints of dense urban environments. Hotel rooms are reimagined as dynamic spaces capable of serving multiple purposes;, such as sleeping, working, dining, and socializing, within a compact footprint. Through an extensive literature review and critical analysis of pioneering micro-hotel case studies like Citizen M, Zoku, and YOTEL, the study identifies key design principles that enable spatial adaptability without compromising comfort or aesthetics Core findings reveal that the integration of modular construction techniques, multifunctional furniture, and smart technology are essential in creating adaptive environments. These systems enhance spatial performance while empowering users to personalize their experience. The research also examines how modularity supports operational efficiency, sustainability, and rapid deployment in the hospitality sector The research culminates in a set of design recommendations for urban micro-hotel development that embraces human-centered innovation, modular planning, and spatial versatility. By aligning design solutions with contemporary urban living trends, this study contributes to the broader discourse on compact, resilient, and responsive hospitality spaces Ultimately, the research provides a framework for designing future-ready hotel environments that respond to evolving guest needs and urban challenges
Keywords: Adaptive hospitality; Modular Design; micro-hotel; spatial flexibility; urban accommodation